Corrosion protection of carbon steel by silica-based hybrid coatings containing cerium salts: Effect of silica nanoparticle content - Santana, Ianina Cecilia (2015)
One strategy for minimising corrosive attack on carbon steel involves the application of hybrid coatings rich in rare earths, on the basis of their low toxicity and environmental sustainability. Tetraethoxysilane (TEOS) and 3-glycidoxypropyl-trimethoxysilane (GPTMS) were each used here as precursors, together with various quantities of colloidal silica suspension, to improve barrier properties of the coatings. Ce(NO3)3·6H2O was added as a source of Ce(III) for further inhibition of corrosion. The corrosion resistance of each kind of sample was evaluated using potentiodynamic polarisation measurements and electrochemical impedance spectroscopy (EIS) in 0.35wt.% NaCl solution. The electrochemical behaviour at various immersion times was modelled by equivalent circuits to demonstrate the effect of silica nanoparticle loading on corrosion. Additional testing was performed under harsh conditions of salt spray chamber. The microstructure and composition of sol-gel coatings were characterised by scanning electron microscopy and energy dispersive X-ray spectroscopy (SEM/EDS), focused-ion beam SEM/EDS analysis, X-ray photoelectron spectroscopy and confocal microscopy.